La reivindicación del mensaje revolucionario en la poesía carcelaria argentina (1976-1983) - Amandine Guillard (Caravelle)
This article offers an overview of the poetry written within the prisons of the last Argentinian dictatorship (1976-1983) by authors who were convicted for political reasons. Although not all prisoners were actually involved in politics before being detained, many of them were and felt the need to continue their activism in prison, in spite of the physical as well as psychological pressures they endured. So, we notice that many convicted poets materialized concerns linked to activism in their writings. We therefore want to analyze how some of them claim the land as the symbolic representation of their struggle and how they turn to poetry to spread the revolutionary message.